Effects of Filipin on the Structure and Biological Activity of Enveloped Viruses - Majuk, Zenowij (1977)
The interaction of the polyene antibiotic filipin with membrane-bound cholesterol in vesicular stomatitis (VS), influenza, and Rauscher leukemia virions was studied. Exposure of virions to filipin resulted in a series of depressions and ridges in the envelope of VS virions, with a periodicity of 15 to 20 nm perpendicular to the long axis of the particle; similar morphological alterations were observed in negatively stained preparations, in thin-sectioned virions, and in protease-treated virions that lack surface glycoproteins. This morphological effect was specific for filipin, since the envelopes of VS virions that had been treated with another polyene antibiotic, amphotericin B, exhibited markedly different morphology. Morphological alterations induced by filipin in influenza and Rauscher leukemia virions differed from those seen in VS virions. The infectivity of filipin-treated VS virions was reduced up to 500-fold, whereas influenza virions were resistant to filipin treatment. Incorporation of filipin into the virions was demonstrated, and no release of either lipids or proteins from virions was detected after filipin treatment. A stoichiometry of approximately 1 mol of bound filipin per mol of cholesterol was found in both intact and protease-treated VS virions. The equilibrium dissociation constant for filipin-cholesterol interaction was approximately 74-fold larger in intact than in protease-treated VS virions. The initial rate of association of filipin with cholesterol in intact virions was slower than that in protease-treated particles. The fluidity of lipids in VS viral membranes, as probed by a stearic acid derivative spin label, was markedly reduced when either intact or protease-treated virions were treated with filipin.